Nanocatalyst Decorated Metal Oxides on Highly Selective Chemical Sensors - 정지원; 장지수 (한국센서학회, 2022)
The accurate detection of environmental and biomarker gas species has attracted increasing attention due to their broad applications, such as air quality monitoring, disease diagnosis, and explosive chemicals detection. To accurately detect target gas species usingchemiresistive gas sensors, using nanocatalysts on semiconducting metal oxides (SMOs) is considered the most promising approach. This review summarizes recent studies on methods for nanocatalysts functionalization on SMOs to achieve the highly selective gas sensors. To this end, we discuss various nanocatalyst decorated metal oxide-based chemiresistive gas sensors and provide an insight to construct highly accurate gas sensors.